2017
DOI: 10.1371/journal.pone.0183730
|View full text |Cite
|
Sign up to set email alerts
|

Impact of post-dialysis calcium level on ex vivo rat aortic wall calcification

Abstract: ObjectivesVascular calcification is a frequent complication in chronic haemodialysis patients and is associated with adverse outcomes. Serum calcium and phosphate levels and imbalances in calcification regulators are thought to contribute to the process. In this regard, the dialysate calcium concentration is a modifiable tool for modulating the risk of vascular calcification. We explored pre-and post-dialysis phosphate and calcium concentrations in stable chronic haemodialysis patients treated by dialysis with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…Each patient underwent a conventional, purely diffusive 4 hour (mid-week) hemodialysis session without hemodiafiltration, using a high flux helixone dialyzer (Fresenius, CUF, 59 mL/h/mmHg; surface, 1,8 m 2 ) and Dialysis Machine Fresenius 5008 in acetate-acidified bicarbonate dialysis, according to previous studies 3,4,7 . In case of citrate-acidified bicarbonate dialysis, high flux helixone dialyzer (Polyflux 21H, Gambro, CUF 78 ml/min/ mmHg, surface 2.1 m 2 ) and Dialysis Machine Artis Baxter were used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each patient underwent a conventional, purely diffusive 4 hour (mid-week) hemodialysis session without hemodiafiltration, using a high flux helixone dialyzer (Fresenius, CUF, 59 mL/h/mmHg; surface, 1,8 m 2 ) and Dialysis Machine Fresenius 5008 in acetate-acidified bicarbonate dialysis, according to previous studies 3,4,7 . In case of citrate-acidified bicarbonate dialysis, high flux helixone dialyzer (Polyflux 21H, Gambro, CUF 78 ml/min/ mmHg, surface 2.1 m 2 ) and Dialysis Machine Artis Baxter were used.…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples before and after hemodialysis were collected in heparin-containing tubes and centrifuged at 5000 rpm for 5 min at 4 °C, according to previous studies 3,4,7 . Plasma samples were frozen in liquid nitrogen and stored at −80 °C until further use, as previously studies 3,4 . This study was conducted according to the Declaration of Helsinki and was approved by the Ethics Committees of Research of University Hospital Fundación Jiménez Díaz (Madrid, Spain) and University Hospital 12 de Octubre (Madrid, Spain).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apo −/− mice with 5/6 nephrectomy displayed aortic valve calcification 12 weeks after surgery both when fed a high phosphate diet as well as a control diet, though with increased calcium deposits detected upon high phosphate diet [36]. Additionally, elevated calcium levels triggered calcification in human VSMC in vitro as well as ex vivo studies with rat aortic rings [38,40].…”
Section: Effect Of the Identified Substances On Cardiovascular Calcifmentioning
confidence: 98%
“…The calcium-phosphate metabolism is one of the key factors for initiation and progression of vascular calcification in CKD [60] and in vitro as well as ex vivo studies showed increased calcification upon increased levels of calcium [38,40] or inorganic phosphate [29,32,33,35]. In late stage CKD (CKD 4-5), most of CKD patients present with hyperphosphatemia [61,62].…”
Section: Mechanisms and Signalling Pathways Associating Uremic Toxinsmentioning
confidence: 99%